Reflection of Pre-Service Physics Teacher on The Implementation of The New Indonesia Curriculum - Muhammad Rezki Irawan; Bibin Sentana Bintang Ramadhan; Lambang Subagiyo; Nurul Fitriyah Sulaeman (Journal of Mathematics Science and Computer Education, 2024)
This study aims to explore the pre-service of physics teachers in implementing the Merdeka Curriculum in the Samarinda region. The Curriculum Merdeka is a learning approach that gives teachers freedom in choosing methods and approaches that use a descriptive method to collect data from prospective physics teachers in Samarinda. The results indicated that most pre-service physics teachers were ready to implement the Merdeka curriculum (76.13%) and acknowledged its effectiveness (73.40%), but some still faced difficulties (64.40%) due to limited direct implementation experience. The study employed a qualitative research approach with a descriptive analysis, used questionnaires as data collection instruments, and employed data analysis techniques such as transcribing, coding, and inference or verification for those who had difficulty implementing the Merdeka Curriculum. This is because pre-service physics teachers have not directly implemented the Merdeka Curriculum. These results indicate that socialization and training on the Merdeka Curriculum alone are not enough; a consistent support program is needed, as are in-depth courses on the Merdeka curriculum as well as apprenticeship programs in schools that implement the Merdeka curriculum for prospective teachers.